AST/ASTS Workshop on Increasing Organ Donation in the United States: Creating an "Arc of Change" From Removing Disincentives to Testing Incentives. Issue 5 (31st March 2015) - Salomon, D. R.; Langnas, A. N.; Reed, A. I.; Bloom, R. D.; Magee, J. C.; Gaston, R. S.; ,
Abstract : The American Society of Transplantation (AST) and American Society of Transplant Surgeons (ASTS) convened a workshop on June 2–3, 2014, to explore increasing both living and deceased organ donation in the United States. Recent articles in the lay press on illegal organ sales and transplant tourism highlight the impact of the current black market in kidneys that accompanies the growing global organ shortage. We believe it important not to conflate the illegal market for organs, which we reject in the strongest possible terms, with the potential in the United States for concerted action to remove all remaining financial disincentives for donors and critically consider testing the impact and acceptability of incentives to increase organ availability in the United States. However, we do not support any trials of direct payments or valuable considerations to donors or families based on a process of market‐assigned values of organs. This White Paper represents a summary by the authors of the deliberations of the Incentives Workshop Group and has been approved by both AST and ASTS Boards. Abstract : The authors present the output of a recent AST/ASTS workshop focusing on challenges facing organ donation in the US, specifically introducing an operational "arc of change" strategy to address removal of all disincentives for living donors and exploring the potential of highly controlled pilot studies of incentives for donation. Read two related viewpoints on pages1180 and1187 .